Challenges applying the research on periodization - Cissik, J.; Hedrick, A.; Barnes, M. (Strength and Conditioning Journal, 2008)
The principles of periodization are commonly used in the design of strength and conditioning regimes for athletes. Researchers examining its effectiveness have found it to be more effective than nonperiodized approaches to training. However, research on periodization surprisingly limited in scope and this makes its application challenging. By broadening subject selection, incorporating longer term studies, incorporating modes of exercise and by conducting observational and survey studies, the research can be made mroe applicable to real-world coaching.